1998
DOI: 10.1046/j.1472-765x.1998.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157 serology: false-positive ELISA results caused by human antibodies binding to bovine serum albumin

Abstract: H . C HA R T, J. E VA NS , R. M. C HA LM E RS AN D R. L. S AL MO N . 1998. An analysis of farm workers and rural dwellers for serum antibodies to the lipopolysaccharide (LPS) of Escherichia coli O157 detected sera with antibodies binding to bovine serum albumin (BSA) by ELISA. These antibodies were not specific for BSA when examined by immunoblotting, and the ELISA values were reduced to a background level when plates were blocked with normal rabbit serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For example, in a study that was examining for the presence of human antibodies to Japanese encephalitis virus, antibodies that cross-reacted with BSA were found (Konishi et al, 2010). Another study found that human antibodies non-specifically bound to BSA (A2153 (≥ 96% pure preparation from Sigma)) (Chart et al, 1998). To prevent falsepositive results from either cross reactive antibodies or from non-specific binding of ELISA reagents to BSA, alternative blocking agents can be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study that was examining for the presence of human antibodies to Japanese encephalitis virus, antibodies that cross-reacted with BSA were found (Konishi et al, 2010). Another study found that human antibodies non-specifically bound to BSA (A2153 (≥ 96% pure preparation from Sigma)) (Chart et al, 1998). To prevent falsepositive results from either cross reactive antibodies or from non-specific binding of ELISA reagents to BSA, alternative blocking agents can be used.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent falsepositive results from either cross reactive antibodies or from non-specific binding of ELISA reagents to BSA, alternative blocking agents can be used. Examples include rabbit serum (Chart et al, 1998), casein (Konishi et al, 2010), heat-denaturing the blocking protein (Mauracher et al, 1991), non-protein blocking solutions like Synblock (Afrough et al, 2007) or Ficoll or polyvinylalcohol (Huber et al, 2009). Alternatively, no protein can be included in the blocking buffer (Jorgensen et al, 2005), although this too can potentially cause artifactual results (Bird et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…were Cryptosporidium parvum (previously referred to as C. interfere with the test (Venkatesan & Wakelin 1993;Chart et al 1998). The studies by and Mead et al (1988) used western blotting that enabled identification of important antigen molecules.…”
Section: Discussion Of Early Worldwide Studiesmentioning
confidence: 99%
“…A note of caution, however, is that the method used requires blocking non-specific binding with BSA, to which dairy farmers may have antibodies (Chart et al 1998). …”
Section: Early Worldwide Studiesmentioning
confidence: 99%
“…The simplest explanation may be insufficient purity of an antigen used for microplate coating, or too low initial sample dilution before the test (especially in the case of relatively low cut-off value). Some authors suggested that non-specific binding of serum antibodies with some blocking agents used in ELISA production may occur (Chart et al, 1998;Konishi et al, 2010). The reason for the occurrence of false-positive results in non-competitive ELISAs may also be attributed to a phenomenon known as a bridging by heterophilic antibodies (e.g.…”
Section: Discussionmentioning
confidence: 99%